Agricultural Land in India: Providence of Farmers - Fulmali, Kanchan (SFIMAR Research Review, 2016)
All the farmers’ leaders collectively burned the "Land Acquisition and Resettlement and Rehabilitation Act 2011", which is currently high on the national political agenda. In India, agricultural business is now in a critical situation and the positions of the farmers are despicable. They are pushed to even commit suicide. At this rate, there will be only a small number of farmers left in the country very soon. There are various reasons for their suicide, as well as their under- development and one of the reasons is various types of land and the challenges each of them pose. They have to face many challenges for their survival. The study is focusing on the types of land which reduces their income and poverty of farmers from Vidarbha which is the cause for their suicide. With the main objective that to find out the types of land is the reason for the farmer’s suicide and to find out the types of land in Vidarbha and their income, the data is collected through various secondary sources and primary sources like interviews taken by the few farmers and questionnaires, where asks a few questions to the 60 farmers from the Vidarbha area covering three districts mainly Amravati, Yavatmal and Nagpur for this research study. After evaluation of the Hypothesis that "Types of Indian land is deciding providence of farmers," few recommendations have been given in the research paper. This study is to find reasons for farmer’s suicide in Vidharbha region and based on various parameters like types of land, income of farmers, government policies etc. This study aims to report the findings from an exploratory study conducted by primary and secondary research.